Immunogold characteristics of VGLUT3‐positive GABAergic nerve terminals suggest corelease of glutamate. Issue 18 (1st July 2015) - Stensrud, Mats Julius; Sogn, Carl Johan; Gundersen, Vidar
<x xml:space="preserve">Abstract</x> There is compelling evidence that glutamate can act as a cotransmitter in the mammalian brain. Interestingly, the third vesicular glutamate transporter (VGLUT3) is primarily found in neurons that were anticipated to be nonglutamatergic. Whereas the function of VGLUT3 in acetylcholinergic and serotoninergic neurons has been elucidated, the role of VGLUT3 in neurons releasing gamma‐aminobutyric acid (GABA) is not settled. We have previously shown that VGLUT3 is found together with the vesicular GABA transporter (VIAAT) on synaptic vesicle membranes in the hippocampus. Now we provide novel electron microscopic data from the rat hippocampus suggesting that glutamate is enriched in inhibitory nerve terminals containing VGLUT3 compared to those lacking VGLUT3. The opposite was found for GABA; VGLUT3‐positive inhibitory terminals contained lower density of GABA labeling compared to VGLUT3‐negative inhibitory terminals. In addition, semiquantitative confocal immunofluorescence showed that N‐methyl‐D‐aspartate (NMDA)‐receptor labeling was present more frequently in VGLUT3‐positive/VIAAT‐positive synapses versus in VGLUT3‐negative/VIAAT‐positive synapses. Electron microscopic immunogold data further suggest that NMDA receptors are enriched in VGLUT3 containing inhibitory terminals. Our data reveal new chemical characteristics of a subset of GABAergic interneurons in the hippocampus. The analyses suggest that glutamate is coreleased with GABA from hippocampal basket cell‐synapses to act on NMDA receptors. J. Comp. Neurol. 523:2698–2713, 2015. © 2015 Wiley Periodicals, Inc.